Plunging into the wave’s ebb: Sufi words, biographies of humanity - Elena Biagi (Altre Modernità, 2016)
Inherent in the meaning which the word ‘identity’ bears in Arabic (huwiyya) is a perception of the human self as an ideal place for both stability and change, both sense of belonging and openness to diversity. Such a dichotomy represents a potentially unique source of intercultural dialogue, when it contributes to shaping ‘identities in motion’, stirred by an unyielding desire for self realization and knowledge. Nevertheless, individual and communal selves develop within the framework of distinctive cultures, moulding their path to identity into collectively shared discourses and representations. In this perspective, the paper aims at highlighting the connection between classical Sufism, generally interpreted as Islamic mysticism, and the concept of identity, looking at how the latter relates to the Islamic spiritual tradition as handed down in the works of some representative medieval Sufis. Furthermore, by dealing with issues ranging from the use of language to themes of love and knowledge, this work intends to emphasize the role of the spiritual dimension as the base for those universal values which are at the core of multicultural societies, and to illustrate how the process of acquiring personal inward awareness can improve intrapersonal relationships while spurring an active participation in social life.